2022
DOI: 10.1186/s40813-022-00253-2
|View full text |Cite
|
Sign up to set email alerts
|

Study on the influence of different production factors on PSY and its correlation

Abstract: Background Finding out the key reproductive performance factors, affecting piglets weaned per sow per year (PSY) can improve the production efficiency and profitability of pig farms. The objective was to understand the actual distribution of different production factors and PSY of breeding pig farms, analyze the correlation to find the main production factors affecting PSY, and formulating a Production Efficiency Improvement Plan in practice. Data included 603 breeding pig farms from September … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In our study, we found five productive factors with the highest correlation with FEI (Table 2). Targeted improvement of these factors may help improve the productivity of commercial pigs, including appropriate nutrition, reasonably supplemented additives, good care at the early nursing stage, special attention to slow-growing pigs, pig health management (control and prevention of viral infections and secondary bacterial infections), correct housing conditions (environmental temperature and ventilation), available bio-security measures, appropriate immunization procedures and regular staff training 14,20,[28][29][30][31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found five productive factors with the highest correlation with FEI (Table 2). Targeted improvement of these factors may help improve the productivity of commercial pigs, including appropriate nutrition, reasonably supplemented additives, good care at the early nursing stage, special attention to slow-growing pigs, pig health management (control and prevention of viral infections and secondary bacterial infections), correct housing conditions (environmental temperature and ventilation), available bio-security measures, appropriate immunization procedures and regular staff training 14,20,[28][29][30][31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…The automatic feeding system, mechanical ventilation system, formula of standardized feed and mating schedule of these farms were described in a previous study [ 8 ]. The farms were from 20 provinces, located in seven regions of the country, namely, East China (40.5%), North China (3.8%), South China (15.2%), Central China (8.9%), Northwest (15.2%), Northeast (5.1%) and Southwest (11.4%) regions.…”
Section: Methodsmentioning
confidence: 99%
“…The collection and authorization of these production data in this study were described before [ 8 ]. This study analyzed 291 large-scale (750–5,800 sows) pig farms for the whole year of 2021.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation